Central nervous system varicella zoster vasculopathy in an immunocompromised patient - Guedes, M (2019)
Central nervous system (CNS) vasculopathy associated with Varicella Zoster Virus (VZV) infection, usually manifesting as stroke due to ischemic lesions by involvement of small arteries, is frequently misdiagnosed. Immunocompromised patients have a particularly higher risk of severe disease and also CNS involvement during or following VZV presentations. We report a case of an 84-year-old man, with myelodysplastic syndrome, who presented with herpes zoster ophthalmicus complicated with left periocular cellulitis and an abnormal neurological exam. Intravenous treatment with acyclovir and amoxicillin/clavulanic acid was began. VZV DNA was detected in the cerebrospinal fluid (CSF) and brain magnetic resonance imaging revealed three acute ischemic lesions in the left frontal and both cerebellar lobes. A VZV CNS multifocal vasculopathy was diagnosed and treatment with intravenous acyclovir continued for 21 days. Immunocompromised patients with VZV infection can have a more severe course of disease with disseminated involvement and multifocal vasculopathy. In these patients the CSF detection of anti-VZV IgG as well as VZV DNA can be helpful in the diagnosis of CNS VZV vasculopathy. The antiviral treatment can improve the outcome and should be adjusted taking in consideration the degree of immunosuppression. This clinical case and review of the literature highlights the challenges in the diagnosis and management of VZV CNS vasculopathy in immunocompromised patients.